ANALISIS PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM MENCIPTAKAN LINGKUNGAN KERJA YANG NYAMAN BAGI KARYAWAN DI PT INDOFOOD SUKSES MAKMUR TBK. DIVISI BOGASARI TANJUNG PRIOK, JAKARTA UTARA - Salsabila Putri Herdiana; Lia Asmalah (Al Hasanah Barokah Foundation, 2025)
This study aims to analyze the implementation of the Occupational Safety and Health (OHS) program at PT Indofood Sukses Makmur Tbk. Bogasari Division, Tanjung Priok, and its contribution to creating a comfortable work environment. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation of managers, OHS staff, and compensation and benefit managers. The results of the study indicate that the company has consistently implemented the OHS program, including the provision of personal protective equipment (PPE), routine health checks, safety training, and periodic OHS audits. Although there are still challenges in the form of the need to improve employee discipline in the use of PPE, this presents an opportunity for the company to continue strengthening supervision, improving compliance, and optimizing communication related to occupational safety. The SWOT analysis places the company's strategy in quadrant II (ST), which indicates that the company has great potential to maximize existing strengths in facing challenges, so that the quality of OHS implementation can be further improved.